2022
DOI: 10.1007/s00520-022-07178-0
|View full text |Cite
|
Sign up to set email alerts
|

Counting the social, psychological, and economic costs of COVID-19 for cancer patients

Abstract: Purpose Cancer patients were particularly vulnerable to the adverse impacts of the COVID-19 pandemic given their reliance on the healthcare system, and their weakened immune systems. This systematic review examines the social, psychological, and economic impacts of COVID-19 on cancer patients. Methods The systematic search, conducted in March 2021, captures the experience of COVID-19 Wave I, when the most severe restrictions were in place globally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 64 publications
1
15
0
2
Order By: Relevance
“…48 The body's ability to mount an immune response against viral infections can be hindered by these comorbidities, which can disrupt the normal function of the immune system. [49][50][51] The increased risk of pneumonia, ICU stay, intubation, and death among diabetic patients in the Mexican cohort may be explained by the weakened immune system and association with other comorbidities. [52][53][54] The association between diabetes and worse outcomes in URIs has been attributed to a number of epidemiological explanations, one of which is COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 The body's ability to mount an immune response against viral infections can be hindered by these comorbidities, which can disrupt the normal function of the immune system. [49][50][51] The increased risk of pneumonia, ICU stay, intubation, and death among diabetic patients in the Mexican cohort may be explained by the weakened immune system and association with other comorbidities. [52][53][54] The association between diabetes and worse outcomes in URIs has been attributed to a number of epidemiological explanations, one of which is COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and damage to blood vessels and tissues, including those in the respiratory system, can result from high blood sugar levels, making it more difficult for the body to fight off infections 48 . The body's ability to mount an immune response against viral infections can be hindered by these comorbidities, which can disrupt the normal function of the immune system 49‐51 . The increased risk of pneumonia, ICU stay, intubation, and death among diabetic patients in the Mexican cohort may be explained by the weakened immune system and association with other comorbidities 52‐54 …”
Section: Discussionmentioning
confidence: 99%
“…Las recomendaciones sanitarias como limitar las interacciones sociales o el distanciamiento social podrían haber contribuido a que los pacientes oncológicos y sus personas cuidadoras experimentaran soledad no deseada (8) o ausencia de soporte ante el temor a un posible contagio. Además, un estudio (15) reportó que la mayoría de los pacientes oncológicos no aceptaban visitas en sus domicilios. La sensación de soledad no deseada podría verse amplificada por ver las calles y comercios vacíos, lo cual era una de las fuentes de preocupación de la población oncológica.…”
Section: Discussionunclassified
“…Por otro lado, se ha reportado que los pacientes diagnosticados de cáncer han experimentado niveles superiores de ansiedad y depresión respecto a la población general debido a los retrasos que han tenido las citas médicas durante la pandemia (12)(13)(14) . Una encuesta aplicada en 16 países europeos constató que el 71% de los pacientes oncológicos estaban bastante intranquilos por el miedo al avance o progresión de la enfermedad, debido a la cancelación o demora que estaban sufriendo con respecto a las citas y revisiones médicas (15)(16)(17) .…”
Section: Introductionunclassified
“…Due to taking over a large part of the medical care system during the COVID-19 epidemic, cancer patients were severely affected by this pandemic. The most common mental concern in cancer patients during the pandemic period were the worry and/ or fear around getting COVID-19 (27). Several studies reported increased anxiety in cancer patients during the pandemic (27,28).…”
Section: The Social and Economic Impacts Of The Covid-19 Pandemic On ...mentioning
confidence: 99%